(untitled) (Journal of Global Accounting, 2024)
Amidst the global shifts brought by the COVID-19 pandemic, businesses are navigating a transformative landscape, compelling a paradigm shift towards digitalization. This abstract delves into the paramount role of digital transformation in the post-pandemic era, exploring facets of technological innovation, organizational adaptation, and cultural evolution. Synthesizing insights from scholarly sources, it investigates the rapid digital trends triggered by the pandemic and delves into challenges encountered by businesses in this transformative journey. Emphasizing the pivotal importance of digital transformation, the abstract underscores its contribution to enhancing resilience, navigating unforeseen challenges, improving customer experiences, and facilitating data-driven decision-making. Acknowledging inherent challenges, a well-defined digital strategy emerges as a determining factor for success. In navigating the evolving business landscape, this abstract seeks to provide a comprehensive understanding of the significance of digital transformation in fostering organizational agility and ensuring long-term success.